Effect of hydrogen addition on the combustion characteristics of premixed biogas/hydrogen-air mixtures. (20th May 2021) - Benaissa, Sabrina; Adouane, Belkacem; Ali, S.M.; Mohammad, Akram
Abstract: The current work presents computational investigations of biogas-hydrogen blends' combustion characteristics for various thermo-physical conditions relevant for practical combustor applications. The numerical simulations were performed using 0-D SENKIN and 1-D PREMIX codes, whereas chemical kinetics is modelled using the GRI Mech 3.0 mechanism. Biogas composition represented by 60CH4 /40CO2 % (v/v) is blended with different H2 concentration varying from 0 to 50% (v/v) in the fuel. The effect of initial temperature and pressure on ignition delay, laminar flame speed ( S u ), flame temperature ( T ad ), species concentrations ( C i ), and heat release rate profiles is investigated. The results showed that GRI-Mech 3.0 predictions are in good agreement with the available experimental ignition delay data for CH4 /CO2 -air mixture for stoichiometric ambient condition ( P = 0.1 MPa and φ = 1). For the high-temperature oxidation, GRI-Mech 3.0 has accurately predicted S u available from literature for pure biogas ( R H = 0.0) under a wide range of equivalence ratios ( φ = 0.7–1.4) for ambient conditions. The computational analysis was then extended for R H ranging from 0.0 to 0.5 over a wide range of equivalence ratio ( φ ) = 0.7–1.4, initial temperatures ( T ) = 300–600 K and initial pressures ( P ) = 0.1–7.0 MPa. These results obtained were used to develop a new analytical correlation for the laminar flame speed ( S u = S u o ( φ, R H ) T T u α ( φ ) P P u β ( φ, R H ) ) in terms of operating conditions. The results show that hydrogen addition to the biogas improves both the flame speed and ignition delay. The extent of reduction in flame speed due to elevation of initial pressure is a linear function of hydrogen addition to biogas. Furthermore, the sensitivity analysis was studied to assess the influence of hydrogen added to the biogas using laminar flame speed sensitivity coefficient ( σ ). The understanding of these mixtures' combustion characteristics at given initial conditions leading to feasibility conformity of optimal blends of biogas/hydrogen mixtures for the design improvement of practical combustors is discussed. Highlights: New analytical correlation for biogas/H2 -air S u (= S u o ( φ, R H ) ( T T u ) α ( φ ) ( P P u ) β ( φ, R H ) ) for combustor relevant conditions. 5 to 10 times reduction in ignition delay with 10–50% H2 addition to biogas (60CH4 /40CO2 ). 2 to 3 times increase laminar flame speed ( S u ) with 10–50% H2 addition to biogas. 2 to 3 times increase in HRR peak with 50% H2 addition to biogas ( T = 300 & 600 K). 1.5 to 2 times increase in peak H and OH peak radials with 50% H2 addition to biogas.